PERBANDINGAN pH DAN KADAR GULA PEREDUKSI DARI SUSU FERMENTASI PROBIOTIK MENGGUNAKAN STARTERLactobacillus casei subsp. casei R-68 DANLactobacillus casei strain ShirotaSELAMA PROSES PENYIMPANAN DINGIN - Raidinawan, Aulia Reza; Pato, Usman; Yusmarini, Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to compare the pH and reducing sugar contentby probiotic fermentation of milk use starter Lactobacillus casei subsp. casei R-68 andLactobacillus casei strain Shirota during cold storage process. This research was done by experiment with to comparing the pH and reducing sugar content by probitic fermentation of milk use starterLactobacillus casei subsp. casei R-68 andLactobacillus casei strain Shirota during cold storage process. In this case, including M0 (cold storage week 0), M1 (cold storageweek 1), M2 (cold storage week 2), M3 (cold storage week 3), M4 (cold storageweek 4), M5(cold storage week 5), and M6(cold storage week 6). The result showed that Lactobacillus casei subsp. casei R-68 stored logical storage averaged for 0-6 weeks foracidity (pH) is4.70-3.47 and reducing sugar content is 34.36-25.50%. While for Lactobacillus casei strain Shirota obtained average cold storage for 0-6 weeks for acidity (pH) 5.32-4.17 and reducing sugar content is 34.51-25.32%. Keywords : Cold storage, Lactobacillus casei subsp. casei R- 68, Lactobacilluscasei strain Shirota, probiotic fermented milk.